LIKEN AMILOIDOSIS DENGAN TERAPI TOPIKAL KOMBINASI (PERDOSKI, 2020)
Cutaneous lichen amyloidosis is a subtype of primary localized cutaneus amyloidosis developed as a result of amyloid mass deposition in dermal papilla. It is usually found without organ involvement. The main characteristic of primary localized cutaneous amyloidosis is the discrete pruritic, hyperkeratotic, and hyperpigmented papules,. This is a case report of 35 years old female, presented with pruritic hyperpigmented papules, hyperkeratosis on her right and left limbs, since 5 years ago. Histopathology examination revealed lichen amyloidosis. She was treated with a combination of topical treatment which gave a good result. Cutaneous lichen amyloidosis is a rare entity, and the treatment for this condition is still a challenge for clinicians due to its persistence and recurrency. The combination potent topical corticosteroid, 6% salicylic acid mixed and diluted spirits, was applied twice a day. The treatment was resumed for 3 months, where it was effective for regressing and clearing the lesion.